2016
DOI: 10.1002/adom.201500701
|View full text |Cite
|
Sign up to set email alerts
|

A Surface Plasmon Enhanced Near‐Infrared Nanophotodetector

Abstract: In this work, we present a plasmonic near infrared light photodetector for the detection of 980 nm illumination. The plasmonic photodetector is fabricated by modifying single layer graphene (SLG)/InP Schottky junction diode with SiO2 encapsulated gold nanorods (SiO2@AuNR), which can confine the incident NIR light by inducing obvious localized surface plasmon resonance, according to theoretical simulation based on finite element method. This study shows that after decoration with plasmonic SiO2@AuNR, the device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…44,45 The maximum D* for our PPy-NPs/Pt device can reach 1.1*10 11 Jones, which is comparable with some InGaAs PDs (D* = 1*10 10 -1*10 13 Jones) and nanostructured PDs (D* = ~ 1*10 8 -1*10 14 Jones). [46][47][48] Compared with commercial PDs 46,48 and some nanoparticle-based ones 10,[49][50][51][52] , this PPy-NPs/Pt hybrid PD is competitive in photodetection range, responsivity and response time, as summarized in Table 1. Notably, PPy-NPs/Pt hybrid PD reveals both faster photoresponse and slightly larger photoresponsivity than PPy-NPs/thermistor PD, although the size of Pt pattern is much smaller than that of NTC thermistor.…”
Section: Resultsmentioning
confidence: 99%
“…44,45 The maximum D* for our PPy-NPs/Pt device can reach 1.1*10 11 Jones, which is comparable with some InGaAs PDs (D* = 1*10 10 -1*10 13 Jones) and nanostructured PDs (D* = ~ 1*10 8 -1*10 14 Jones). [46][47][48] Compared with commercial PDs 46,48 and some nanoparticle-based ones 10,[49][50][51][52] , this PPy-NPs/Pt hybrid PD is competitive in photodetection range, responsivity and response time, as summarized in Table 1. Notably, PPy-NPs/Pt hybrid PD reveals both faster photoresponse and slightly larger photoresponsivity than PPy-NPs/thermistor PD, although the size of Pt pattern is much smaller than that of NTC thermistor.…”
Section: Resultsmentioning
confidence: 99%
“…2016, 4, 763–771. Copyright 2016, John Wiley & Sons ( Luo et al., 2016 ). (D) Crystal structure of monoclinic MoO 2 , and the experimental and theoretical absorbance spectra of MoO 2 nanocrystals with nanosphere and nanorod shapes.…”
Section: Approaches To Nir Light Generationmentioning
confidence: 99%
“…A possible strategy to suppress the toxicity of metal nanostructures is to encapsulate them hermetically within a non-toxic amorphous silica (SiO 2 ) shell ( Wang et al., 2011 ). As shown in Figure 5 C, NIR resonances can be achieved by switching to aspect ratio (namely L/W is defined as the length/width of the nanostructures) of the SiO 2 -coated Au NRs ( Luo et al., 2016 ). When the aspect ratio increases from 3 to 7.5, the NIR absorption band was observed to shift from 700 to 1150 nm.…”
Section: Approaches To Nir Light Generationmentioning
confidence: 99%
“…Luo et al demonstrated that the photodetector device modifying plasmonic Au nanostructures onto the surface of CdTe NW exhibited the obvious photoresponse to 510 nm light illumination, with high response speed and fast recovery time [87]. A high-performance near-infrared (NIR) PD was constructed by coating single layer graphene (SLG)/InP Schottky junction diode with plasmonic SiO 2 @AuNRs; the schematic diagram of the PD and the TEM image of the SiO 2 @AuNRs on SLG film are shown in Figure 5a,b [96]. The decoration of SiO 2 @AuNRs could slightly improve the Schottky junction barrier, resulting in the increased built-in electric field, and then the separation efficiency of carriers was improved.…”
Section: Surface Plasmonic Resonance For Strong Scattering and Absorpmentioning
confidence: 99%
“…(c) Photoresponse of two different devices with and without SiO 2 @AuNRs modification under 980 nm light illumination of 6.7 mW cm −2 without applied bias. (d) Photoresponsivity of the NIR PDs with and without SiO 2 @Au decoration[96].…”
mentioning
confidence: 99%